Формування доданої вартості на промислових підприємствах на етапах руху продукції від виробника до споживача - Брюховецька, Н.Ю.; Чорних, О.В. (Стратегія і механізми регулювання промислового розвитку, 2017)
Висвітлено сутність доданої вартості на макро- та мікрорівнях, проаналізовано визначення доданої вартості підприємств у працях вітчизняних і зарубіжних науковців. Досліджено етапи формування доданої вартості на промислових підприємствах. Встановлено, що для забезпечення формування ланцюга доданої вартості шляхом побудови замкнутого циклу виробництва має застосовуватися вертикальна інтеграція, яку доцільно будувати за допомогою утворення інтеграційних промислових об’єднань. Запропоновано концептуальну модель визначення доданої вартості продукції на кожному з етапів її формування на промислових підприємствах. Освещены сущность добавленной стоимости на макро- и микроуровнях, проанализированы определения добавленной стоимости предприятий в трудах отечественных и зарубежных ученых. Исследованы этапы формирования добавленной стоимости на промышленных предприятиях. Установлено, что для обеспечения формирования цепочки добавленной стоимости путем построения замкнутого цикла производства должна применяться вертикальная интеграция, которую целесообразно строить с помощью образования интеграционных промышленных объединений. Предложена концептуальная модель определения добавленной стоимости продукции на каждом из этапов ее формирования на промышленных предприятиях. The article is devoted to the value added, which is part of the full value of the goods reflects the real contribution of enterprises to the creation of a particular product. Defining the factors that form the added value of products, installed, that material costs do not depend on the efforts of the producers and so they included in the price of goods. Such components as wages, profits, deductions for social events, amortization is value-added because they are the parts of the full value of the goods, which are created on a particular stage in the production process of the product. Analysis of the entire value chain of the product is a tool to improve the efficiency of production activities of the enterprise, as it takes into account the relationship between the manufacturer and external partners in relation to it. Increase added value of products can be achieved through the use of modern energy saving technologies and complex processing of raw materials in industrial enterprises. Possible through the development of integration processes in the industry while creating value added chain of products. With the aim of increasing efficiency production first of all you need to create or expand their own the raw material base, which contributes to improving product quality and reducing prices. Inclusive forms of associations of enterprises contribute to the expansion and deepening of production and technological linkages, sharing of resources, pooling capital, creating favorable conditions for economic activities of enterprises, producing goods with high added value. The conquest of new markets is possible with creating your own retailers. To ensure the effectiveness of cooperation between enterprises for extraction of raw materials, processing and trading enterprises should apply vertical integration, which it is advisable to build through education, integration of industrial associations. Advantage of vertical integration is to ensure the formation of value added chain by building a closed cycle of production with bringing products to the end consumer. Аs the basic scheme of interrelation of links of a full cycle of formation of the added value of production to use the given conceptual model which contains structure and subjects of creation of the added value at each stage of its formation at the enterprises, methods of calculation and sources of creation of the added value.